Identificação e encaminhamento do aluno da educação especial para o atendimento educacional especializado: uma análise bibliométrica - Danubia Carolina Augusto Alves (2021)
The Brazilian Education history is a prize-winning by a series of advances and retreat as at guarantee of the right and permanence of the people with deficiency at the scholar spaces, counting in a lot of moments with participation of the church and medicine, that rated and named the individuals, according to established standards at the most different historic contest. Such classifications indicated the existence of an ideal student and at counterpoint, presented those who to be dianosticated with some disease, disorder or disturb would pass to be named as ‘abnormal’. Dichotomically, while one of the side, can be seen the advance of the educational legislation as the offering of a Special Education. On the other side, have themselves, the ‘advance’ of the medic-clinics diagnostics producing the calling ‘school failure’. So appear a Special Education conducted by a medicalizing slant that passed to condition the school entry through of presentations of reports, diagnostics or forwarding. However, as resource to guarantee for the students the access at the Special Education, when launching the technical note 04/2014, formulated by Continuing Education Secretariat of MEC, the reports presentations, opinions or diagnostics didn’t should be considered determinants for what the forwarding of the student for the Specialized Educational – AEE was realized. At the same time we saw the enlargement for the success at the AEE, establish itself the doubt how to be the mechanism that would pass to be utilized for the students forwarding process. That said, the general objective of this research was to verify through realization of a bibliometrics analyses, how are identified and forwarded the students of the special education to AEE. So that we pay attention first in to identify the researches that have already been realized and made available at the Brazilian digital Library of thesis and Dissertations of the CAPES and BDTD, from 2008, period of institution of National Politic of Special Education at Perspective of Inclusive Education (PNEEPEI). We seek, posteriorly to characterize the profile of the scientific production, aiming guarantee the relevance of the information, in sequence we analyzed the actions of the professional that realize the identification and the forwarding to AEE and/or Multifunctional Resource Room (SRMs). Finally, we analyzed the profile of the Special Education students that are forwarded at AEE and/or Room of Resources. As the research resulted, it turned out that in 80% of the 24 analyzed works, according to the responsible by the forwarding of the students at AEE and, among the most cited deficiencies stands out the Intellectual Deficiency (DI). It was verified yet, that the National Politic of Special Education at perspective of Inclusive Education, instituted in 2008, in itself don’t guarantee the access for the student of special Education, making up necessary the constant involvement of the professionals of the school, family and multidisciplinary teams throughout the process, in the order to enable not only the access to AEE, but the right an Education that can answer to the specifics educational necessities, according to predict the Federal Constitution 1988.